ANALISIS PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI PENGOLAHAN TAHUN 2001-2015 DI PASURUAN DAN SIDOARJO - Muhammad Ardiansyah; Idah Zuhroh; Muhammad Faisal Abdullah (Jurnal Ilmu Ekonomi JIE, 2018)
The number of employment that has been filled and depicted from the number of people who work can be interpreted as the absorption of labor. The purpose of this study is to know and compare the influence of medium and large industry, minimum wage and economic growth on labor absorption of processing industry sector in Sidoarjo and Pasuruan regency. The tool used in this research is multiple linear regression with time series data.The results of this study indicate that the test together (F test), where Fcount> Ftabel that is equal to 679.4531> 3.59 for Pasuruan and 27.85815> 3.59 for Sidoarjo regency which means Pasuruan Regency significantly more significant than Sidoarjo regency. Individually in both districts, the result of Amount of Medium and Large Industries has positive and significant effect on Labor Absorption, Minimum Wage has negative and significant effect on Labor Absorption, and Economic Growth has positive and significant impact on Labor Absorption.Keywords: Employment Absorption, Amount of Unit Industry, Minimum Wage, and Economic Growth.